Eugenia vinculada a aspectos bioéticos: uma revisão integrativa - Santos, Vanessa Cruz; Fonseca, Jamile Guerra; Boery, Rita Narriman Silva De Oliveira; Sena, Edite Lago Da Silva; Yarid, Sérgio Donha [UNESP]; Boery, Eduardo Nagib (Centro Brasileiro de Estudos de Saúde, 2014)
The objective of the study is analyzing the scientific productions that deal about binding- the eugenics with the bioethical issues. This is an integrative literature review. The data were collected in Lilacs and SciELO, through descriptors: eugenics, ethnicity and health, ethics and bioethics. For later analysis and synthesis of the synoptic articles a figure was used. It was found that eugenics violates human rights, contradicts with the principle of solidarity and endangers human diversity. It was concluded that there were articles addressing bioethical issues related to eugenics, thus, this study may contribute to the reflection on this articulation deficit.

O objetivo do estudo é analisar o que versam as produções científicas sobre eugenia, vinculando-as com aspectos bioéticos. Trata-se de uma revisão integrativa de literatura. Os dados foram coletados nas bases de dados Lilacs e SciELO, por meio dos descritores: eugenia, etnia e saúde, ética e bioética. Para a análise e posterior síntese dos artigos foi utilizada figura sinóptica. Verificou-se que a eugenia viola os direitos humanos, contradiz com o princípio da solidariedade e coloca em risco a diversidade humana. Conclui-se que houve déficit de artigos que abordem aspectos bioéticos vinculados à eugenia, assim, este estudo poderá contribuir para a reflexão sobre essa articulação.
Eugenia connection with issues bioethical: an integrative review
Keywords: Eugenics; Ethnicity and health; Ethics; Bioethics; Eugenia (Ciência); Etnia e saúde; Ética; Bioética